Use of the Diffuse Field Assumption (DFA) Method to Determine The Condition of The Subsurface Layer in The Government Office Area of Bengkulu City, Indonesia - Efmadani; Farid, Muchammad; Refrizon; Raihana, Hana; Anggi, Arya Putra; Hasugian, Basdikki; Al-Ansory, Andre Rahmat (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Bengkulu City lies in an earthquake-prone region because of tectonic activity along the Sumatra subduction zone. Subsurface characterization is critical for safe infrastructure planning. This study identifies subsurface conditions in the Bengkulu City Government office area using microtremor data analyzed with the Diffuse Field Assumption (DFA) approach. Researchers recorded 52 measurement points to determine key seismic parameters: dominant frequency (f0), amplification factor (A0), seismic vulnerability index (Kg), and shear wave velocity (Vs30). The results show that f0 values range from 3.57 to 14.8 Hz, A0 from 1.62 to 7.18, Kg from 0.30 to 6.35, and Vs30 from 189.29 to 740.48 m/s, indicating significant spatial variation in subsurface conditions. Areas characterized by low f0, high A0, and low Vs30, particularly at points T33 and T41, are identified as zones with higher seismic vulnerability. The application of the DFA approach enables a more reliable estimation of subsurface shear wave velocity and enhances the interpretation of site effects compared to conventional analysis. These findings highlight the importance of integrated seismic parameter mapping to support earthquake hazard mitigation and urban spatial planning in tectonically active regions.